Clinical outcomes and quality of life 5 years after a randomized trial of concomitant or sequential phlebectomy following endovenous laser ablation for varicose veins. Issue 9 (11th June 2014) - El-Sheikha, J; Nandhra, S; Carradice, D; Wallace, T; Samuel, N; Smith, G E; Chetter, I C
Abstract: Background: Endovenous laser ablation (EVLA) is a popular treatment for superficial venous insufficiency. Debate continues regarding the optimal management of symptomatic varicose tributaries following ablation of the main saphenous trunk. This randomized trial compared the 5-year outcomes of endovenous laser therapy with ambulatory phlebectomy (EVLTAP) with concomitant ambulatory phlebectomy, and EVLA alone with sequential treatment if required following a delay of at least 6 weeks. Methods: Patients undergoing EVLA for great saphenous vein insufficiency were randomized to receive EVLTAP or EVLA alone with sequential phlebectomy, if required. Outcomes included disease-specific quality of life (QoL) (Aberdeen Varicose Vein Questionnaire; AVVQ), requirement for secondary procedures, clinical severity (Venous Clinical Severity Score; VCSS), residual and recurrent varicose tributaries, and generic QoL. Patients were followed up for 5 years. Results: Fifty patients were randomized equally into two parallel groups. The EVLTAP group had lower VCSS scores at 12 weeks (median 0 (i.q.r. 0–1) versus 2 (0–2); P <0·001), and lower AVVQ scores at 6 weeks (median 7·9 (i.q.r. 4·1–10·7) versus 13·5 (10·9–18·1); P < 0·001) and 12 weeks (2·0 (0·4–7·7) versus 9·6 (2·2–13·8); P = 0·015). VCSS and AVVQ scores were equivalent by 1 year, but only after 16 of 24 patients in the EVLA group, compared with one of 25 in the EVLTAP group ( P < 0·001), had received a secondary intervention. From 1 to 5 years both groups had equivalent outcomes. Conclusion: EVLA with either concomitant or sequential management of tributaries is acceptable treatment for symptomatic varicose veins, with both treatments achieving excellent results at 5 years. Concomitant treatment of varicosities is associated with optimal improvement in both clinical disease severity and QoL. Abstract : Simultaneous phlebectomy makes sense